The Existence Of Regional Governments Post-Reform - Permatadani, Ega (Socio Legal and Islamic Law, 2022)
The local government is the organizer of government affairs by the local government, and performs co-administration tasks with the broadest principle of autonomy in the system and principles of the Unitary State of the Republic of Indonesia as referred to in the 1945 Constitution. Autonomy changes many things in this country, and makes it easier to follow the era globalization evolves over time. Autonomy has a role in encouraging a culture of democracy, freedom and making things easier for a business. Representation is a mechanism for applying the normative idea that rulers must be exercised by the will of the people or the will of the people. Autonomous is independent which takes care of its own household without interference from the central government, the people themselves here play a very important role in the success or failure of an implementation of regional autonomy because everything depends on the participation of the people and also the relationship of the rulers. The power that occurs in a government will also depend on whether or not it is able to transform the people's will as a top priority or the highest value above the wishes of a country, where the people are the priority whether the autonomous administration is carried out very well. The existence of local governments is getting stronger and has become commonplace among the people, based on qualitative methods and based on normative legal research. From the many studies on local government, there are many pluses and minuses to the legal politics of local government in this autonomous regime. And all of these rules have actually been regulated in Law Number 23 of 2014 concerning Regional Government, which regulates many regional governments in autonomous regimes. Keywords :Â Local government, people, autonomous.